Anthropozoonotic helminthiases in Australasia: Part 3: - studies on the prevalence and public health implications of helminth parasites of dogs and cats in urban environments - Ng, B. K. Y.; Kelly, J. D. (International Laboratory for Zoonoses - Research Foundation, 1975)
Man has acquired helminth infections at different times during his evolutionary history and animals have and do serve an important role in supplementing these acquisitions. Helminth species are divided into those which accompanied man as he emerger as a species and those which he has since acquired from domestic, wild and domiciliated animals by breakdown of ecological, physiological and immunological barriers (Sprent 1969). With particular reference to helminth zoonoses transmitted through domesticated animals, the role played by dogs and cats in disease transmission to man (in urban environments) has been largely overlooked. In the Australasian region, the most important helminth zoonoses transmitted by dogs and cats in heavily urbanised areas as Toxocara sp., Ancylostoma sp. and Dirofilaria immitis. The prevalence, geographic distribution and major epidemiological considerations for each parasite are discussed with the view that future control and/or eradication programs should be based on a sound epidemiological understanding of the natural life history of the helminths concerned.